Territórios, sociabilidades e territorialidades: o tecer dos fios na realidade dos sujeitos dos distritos de Perus e Anhanguera da cidade de São Paulo - Diniz, Rodrigo Aparecido (2012)
This present study analyzes the mediations in the urban territory through the sociabilities constructions by the subjects, taking as it references the districts of Perus and Anhanguera, in São Paulo City. This research journey were traced by the contribution of the oral history methodology, as the privilege source to approach the subjects dialogue that make and remake lives experiences in their territories, day by day. In this way, we present the three women trajectories. They are communities leaders in the territory of Perus and Anhanguera, whose lives mediated by the pursuit of social protection, as well as centralize their stories in social spaces in these territories, making sociabilities and territories that bring specifics facts of the fight as a continuous process of lives reproduction in the São Paulo s peripheral region. So, the research s narratives not only engender specific analyzes of the studied reality, but perform fruitful dialogue with the theoretical parts that support this dissertationa